2000
DOI: 10.1002/(sici)1097-0215(20000215)85:4<584::aid-ijc22>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2-methoxyoestrone-3-O-sulphamate on the growth of breast cancer cells and induced mammary tumours

Abstract: 2‐Methoxyoestrogens are emerging as a new class of drug that can inhibit tumour growth and angiogenesis. As sulphamoylation of oestrogens enhances their potency and bioavailability we have synthesized 2‐methoxyoestrone‐3‐O‐sulphamate (2‐MeOEMATE) and compared its ability to inhibit the proliferation of breast cancer cells with that of 2‐methoxyoestrone (2‐MeOE1). 2‐MeOEMATE (1 μM) inhibited the growth of oestrogen receptor positive MCF‐7 breast cancer cells by 52% whereas 2‐MeOE1 had little effect at this conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 17 publications
3
43
0
Order By: Relevance
“…39 It has previously been reported that a sulphamoylated analogue, 2-MeOEMATE, also induces BCL-2 phosphorylation in MCF-7 cells, leading to the induction of apoptosis. 24,25 In the present study, it was observed that all the sulphamoylated oestrogen derivatives tested have similar effects on the BCL-2 protein. At 1 lM the sulphamoylated analogues induced extensive phosphorylation of the BCL-2 protein, while 2-MeOE2 induced a lesser degree of phosphorylation.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…39 It has previously been reported that a sulphamoylated analogue, 2-MeOEMATE, also induces BCL-2 phosphorylation in MCF-7 cells, leading to the induction of apoptosis. 24,25 In the present study, it was observed that all the sulphamoylated oestrogen derivatives tested have similar effects on the BCL-2 protein. At 1 lM the sulphamoylated analogues induced extensive phosphorylation of the BCL-2 protein, while 2-MeOE2 induced a lesser degree of phosphorylation.…”
Section: Discussionsupporting
confidence: 51%
“…[24][25][26][27] In MDA-MB-231 cells, while 2-MeOE2 induced a reversible G2-M arrest, the effects induced by sulphamoylated derivatives were irreversible. Similar reversible effects with 2-MeOE2 have also been reported for other cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations